PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPSq) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMPN 4 KOTA BENGKULU - Trihasari, Shelly; Haji, Saleh (Jurnal Pendidikan Matematika (JUPITEK), 2019)
This research aimed to investigate the implementation of cooperative learning model in the type of Think Pair Square (TPSq) in order to improve students’ achievement. The design of the research was a Classroom Action Research with the techniques of collecting the data were through the observation sheet of students’ learning activities and summative test. The subject of the research were the 1st grade students of SMPN 4 Bengkulu City academic year of 2018/2019 with total amount of students were 32 consist of 16 males and 16 females students. The research was conducted in three cycles from 7th September 2018 until 13 October 2018. The result of the research showed that the implementation of cooperative learning model type Think Pair Square improved students’ achievement in Mathematic. Students’ learning activities were improved by giving the students work sheet that contains a completion process so that facilitate students in working on the students work sheet, appreciating the student with applause after they delivered their opinion, and dividing students in heterogenous groups based on their academic skills. The improvement on students’ achievement can be seen from the increasing on the mean of students’ scores from first cycle to third cycle namely: 74.35; 79.91; 81.14 and the percentage of classical learning completeness from first cycle to third cycle is : 76.67%; 83.33%; 93.33%.